An aggressive course of pyoderma gangrenosum mimicking bacterial osteomyelitis after open reduction and internal fixation of a distal radius fracture with a titanium plate - Michał Wasiak; Michał Ciszek; Ireneusz Babiak; Piotr Wasilewski; Paweł Łęgosz; Bartosz Kieroński; Paweł Małdyk (Rheumatology, 2022)
Pyoderma gangrenosum (PG) is a rare condition characterized by the development of aseptic, non-healing skin ulcers. Any skin trauma, such as a surgical incision, can trigger an outbreak of lesions. Our case and literature review show that a physician should consider PG in every event of a non-healing, aseptic wound after surgery. The treatment of PG requires collaboration within a multidisciplinary team and immunosuppressive therapy is the first line of treatment, while surgical interventions should be avoided in the active stage of PG.